TRANSFORMASI LAYANAN PERPUSTAKAAN SEKOLAH MENENGAH KEJURUAN MELALUI SISTEM INFORMASI BERBASIS WEB - Rini Widyastuti; Gusmanila Gusmanila; Karmila Suryani; Ade Fitri Rahmadani; Ashabul Khairi (Jurnal Riset Sistem Informasi, 2026)
The rapid advancement of information technology has driven significant changes in the management of school libraries, particularly in SMK that require efficient access to learning resources. This study addresses the limitations of manual library management at SMK Kartika 1–2 Padang, which resulted in data redundancy, slow information retrieval, and suboptimal reporting processes. The purpose of this research is to design and implement a web-based library information system that can systematically improve the quality and performance of library services. The study employed a system development research approach using the Waterfall model, encompassing requirements analysis, system design, implementation, and testing phases. Data collection was carried out through observation, interviews, and literature review. The results demonstrate that the developed system successfully integrates the management of book collections, member records, borrowing and returning transactions, and automated reporting within a single platform. The implementation of the system significantly enhances service efficiency by reducing processing time, minimizing data duplication, improving accuracy in transaction recording, and enabling faster access to library information for users. The main contribution of this research lies in providing a practical and applicable model of a web-based library information system that effectively improves operational efficiency and service quality in vocational school libraries.